Caracterização e avaliação da fotoestabilidade do filtro solar butil metoxidibenzoilmetano (avobenzona) através de IV e RMN - Sousa, Renato Ribeiro de (2015)
In this paper was performed a characterization of the solar protectors avobenzone and octyl methoxycinnamate and the assignments of its second order coupling. The avobenzone photostability was evaluated in different types of solvents, concentrations and time exposition to UV light. Nevertheless, it was measured the radiation absorption on near and medium infrared in four commercial solar protectors, wherein only one of them claims in its package the guarantee of such protection. The characterization of the solar protector sctructure was made by ¹H NMR using a Bucker Avance III 500 spectrometer. It was used a Gaussian 09 program to calculate and optimize the most stable molecule structure and the coupling constants of protons and the WinDNMR to simulate the theoretical spectra from the data obtained by the calculations. The photostability of the avobenzone was determined by irradiating for 5, 10, 15 and 20 minutes, under a UV lamp, solutions of avobenzone in chloroform, methanol, acetone and acetonitrile in concentrations of 5,32x10-2 mol/L and 1,6x10-3 mol/L, monitoring the alterations occurred by 1H NMR. The absorption in the near and middle infrared regions was made in a PerkinElmer Frontier Dual Range FT spectrometer, where the sample was directly deposited into the equipment, without the need of previous treatment. The theoretical calculation showed itself an important tool to the attribution of second order systems, given that is not possible to manually determine the coupling constant values in this kind of system. The avobenzone presented itself photoinstable in the solution with concentration 1,6 x 103 mol/L, and in acetonitrile. On other solvents the photoinstability wasn’t observed. In the others commercial solar protectors showed similar absorption on the near and middle infrared, not existing significative difference between the product that declared having as a selling point this kind of absorption and the rest, being possible to assert that this information is used in its label for commercial reasons, not being characteristic of quality among the other products.